Variation in training regimens in professional showjumping yards. (29th August 2013) - Lönnell, A. C.; Bröjer, J.; Nostell, K.; Hernlund, E.; Roepstorff, L.; Tranquille, C. A.; Murray, R. C.; Oomen, A.; van, R.; Bitschnau, C.; Montavon, S.; Weishaupt, M. A.; et al.
Summary Reasons for performing study Training regimens of showjumping horses under field conditions are largely undocumented. Objectives The aims of this study were to quantify and compare training regimens used in professional‐level showjumping yards, with respect to time exercised and type of activity. Study design Prospective cohort study. Methods A prospective 6‐month cohort study of showjumping horses in 4 European countries (The Netherlands, Sweden, Switzerland, Great Britain) was designed to analyse training and health data, in yards with several horses in training and riders competing at professional level. Riders documented the daily frequency and duration of all physical activities of the horses. Variation in training routines were compared between riders, location and time. Mixed‐models analysis was used to examine factors associated with total time exercised and time spent in flatwork. Results In 4 countries, the 31 participating riders trained 263 European Warmbloods. The total days at risk (e.g. days in which the horses were considered fit for exercise) was 39, 262. Mean time spent in daily exercise, including ridden work, lungeing and treadmill exercise, varied between riders from 19–52 min/day at risk. There was considerable variation in activities and level of heavy work and light exercise, i.e. turnout. Total time exercised and time spent in flatwork differed with month, country and proportion of days lost to training. Low variation of activities was associated with decreased total time trained and increased time spent in flatwork. Conclusions Riders at this elite professional level of showjumping used training regimens that vary substantially in time spent training and other physical activities and showjumping horses are challenged differently during training despite competing at the same level. Whether all training regimens prepare the horses equally for the demands of competition remains to be determined.